Heat‐Excitation‐Based Triboelectric Charge Promotion Strategy - Xin Xia; Yunlong Zi (Advanced Science)
Abstract The surface charge decay is observed at high temperatures due to thermionic emission, which, however, may not be the only mechanism contributing to the surface charge variation. Here, a triboelectric charge promotion strategy due to the heat‐excitation effect of hot electrons near the fermi level is demonstrated, while the final charge is determined by the balance between thermionic emission and the heat‐excitation effect. It is demonstrated that metals with lower work function exhibit a better heat excitation capability, and polymers with lower fluorine content in molecule chains further boost the charge output, where metal/Kapton pairs demonstrated a charge promotion of over 2 times at the temperature of 383 K with good durability during 90 min measurement. The heat‐excitation effect and charge durability in sliding freestanding‐triboelectric‐layer (SFT) mode triboelectric nanogenerator (TENG) is demonstrated as well, where the energy is promoted by over 3 times and the capacitor charging speed is doubled as well, with an energy promotion from 109.34 to 373 µJ per cycle to successfully trigger a discharger. This work suggests a promising future of the heat‐excitation effect as a new charge promotion strategy for TENG toward different applications in high‐temperature environments.